원유수급 불균형의 원인과 정책과제 - 성동현 (KREI, 2003)
This paper examines the cause of increasing milk powder stocks, analyze the effects of current dairy policy, and suggests the dairy policy to stabilize the milk supply and demand in Korea. One cause of unbalanced milk supply and demand is non-flexible farmgate pricing system not depending on the utilization situations. Also, consumption of fluid milk have stagnated since last decade. Korea Dairy Committee have overextended the milk collecting to one system under the Committee. For alleviating this problem, government have taken actions of slaughtering milking cows, differentiating the pricing system of oversupplied milk, and terminating the dairy farm enterprises. These policies have effects in the short-run, however, this analysis showed that the essential problem of current situation could not be solved in the long-run. As a way of resolving the current oversupply of raw milk, it would be considered that the improvement of raw milk pricing system.
Keywords: 원유; 낙농정책; 원유수급전망; Raw milk; Dairy Policy; Raw milk Supply and Demand outlook